Berbamine ameliorates isoproterenol‐induced myocardial infarction by inhibiting mitochondrial dysfunction and apoptosis in rats. Issue 3 (28th November 2018) - Saranya, Sithuraj; Baskaran, Rathinasamy; Poornima, Paramasivan; Vijaya Padma, Viswanadha
Abstract: Berbamine (BBM), a bisbenzylisoquinoline alkaloid from roots, bark, and stem of Berberis plant such as Berberis aristata has a wide range of pharmacological activities. However, the evidence for the cardioprotective effect of BBM is inadequate and the molecular mechanism of BBM remains unclear. This study investigated the underlying molecular mechanism of BBM‐mediated cardioprotection on isoproterenol (ISO)‐induced mitochondrial dysfunction and apoptosis in rats. The assays of mitochondria antioxidant status, mitochondrial marker enzymes, and electron microscopic analysis of mitochondria revealed BBM significantly prevented the mitochondrial dysfunction induced by ISO. The ISO‐induced elevation of mitochondrial oxidative stress was also curbed by BBM. Furthermore, pretreatment with BBM protected the heart tissue from ISO‐induced apoptosis as evident from decreased terminal dUTP nickend‐labeling positive cells and decreased expression of Bax, cytochrome c, cleaved caspase‐9, and caspase‐3, and poly (ADP‐ribose) polymerase and increased expression of Bcl‐2 in ISO‐induced rats. These current findings suggest that BBM exerts a significant cardioprotective effect on ISO‐induced myocardial infarction in rats. Abstract : Berbamine (BBM) restores ISO‐induced energy depletion and prevents mitochondrial dysfunction. BBM modulates ISO‐induced apoptosis signaling pathway. BBM protects the heart from ISO‐induced cardiotoxicity.